Translation, Gender and the Republic of Letters in José de Cadalso's Los eruditos a la violeta and Its Suplemento*. Issue 3 (16th March 2019) - Harkema, Leslie J.
Abstract: In this article I study José de Cadalso's satirical work Los eruditos a la violeta and its Suplemento (both published in 1772), in relation to the changing understanding of the 'Republic of Letters' in late eighteenth-century Spain. In doing this, I focus particularly on the discussion of translation initiated by a fictional female reader at the beginning of the supplementary text. Arguing that the Suplemento subverts the conception of the literary world presented in the original satire, I first analyse the construction of ideal and unacceptable versions of learned masculinity (that is, 'originals' and 'copies') in Los eruditos . I then show how the letter from the female reader that opens the Suplemento destabilizes this binary understanding of knowledge and forces a reconsideration of the reaches of the literary sphere. In discussing this woman's intervention and her request for translations, I reflect on the historical association of translation with the feminine that casts it as a reproductive rather than a productive mode of writing. In the final section of the article I study the translations that Cadalso includes in the Suplemento, and demonstrate how this addendum offers some steps toward a 'reframing of fidelity' through its nuanced contribution to the debate surrounding translation in eighteenth-century Spain.